Culture, spaces, and people: Urban dynamics in contemporary India - Jain, Daksh; Singh, Binti (London Routledge, 2023)
This volume discusses the nuances of cultural phenomena in the transforming urban landscape of Indian cities. It focuses on the role of globalization, transitioning economic patterns, National Urban policies in changing their urban landscape.
Keywords: Urban policy India; India Social life and customs 21st century; City planning India